GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN LINGKUNGAN KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PLN (PERSERO) DISTRIBUSI JAKARTA RAYA DAN TANGERANG AREA LENTENG AGUNG - SITI ZULFAH, Asri Warnanti (PARADIGMA, 2015)
This research is concerning The Influence Of Leadership Style, Work Discipline and Work Environment On Employee Productivity In PT. PLN (Persero) Distribution Jakarta Raya and Tangerang Area Lenteng Agung. Â The method research used is a causal comparative. The samples taken by The author are 45 respondents based on theory slovin by used value e = 10%. The author used observation, interviews, and questionnaires for the methods of data collection. In the statistic analyst, the author used SPSS program (Statistical Package for The Social Sciences) version 20.00 to search for the validity, reliability, correlation coefficients, multiple determination, multiple regression, test of t and test of F. The data processing is done by SPSS program (Statistical Package for The Social Sciences) version 20.00, the result is r = 0.824 by multiple determination of 67.9% and the balancing is 32.1% shows another factor contribution. For multiple regression values obtained Ã = -2.020 + 0.236X1 + 0.800X2 + 0.027X3 and test of F by É = 5% obtained values Fhitung as 28.894 and values Ftabel as 2.833, that means Fhitung > Ftabel that means Ho is rejected and Ha is a accepted. This shows that there is a significant relationship between Leadership Style (X1), Work Discipline (X2) and Work Environment (X3) together (simultaneously) on Employee Productivity (Y) in PT. PLN (Persero) Distribution Jakarta Raya and Tangerang Area Lenteng Agung.Â Keywords : Leadership Style, Work Discipline, Work Environment, Employee Â Â Â Â  Productivity.